2021
DOI: 10.2147/ott.s290124
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Acanthosis Nigricans with Recurrent Bladder Cancer: A Case Report and Review of Literature

Abstract: Acanthosis nigricans (AN) is a rare cutaneous condition that may be a manifestation of certain endocrinological or autoimmune diseases, as well as a potential marker for underlying undiagnosed cancer. AN is classified as either benign or malignant based on its clinical associations. Malignant acanthosis nigricans (MAN), which tends to be extensive and develops rapidly, is considered to be a paraneoplastic syndrome associated with advanced cancer, commonly accompanied by intra-abdominal malignancies. Bladder ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The prevalence of RAU worldwide ranges from 5% to 66% (Bratel and Hakeberg, 2014), and it is approximately 20% in China (Xu et al, 2021). At present, to reduce the occurrence frequency of RAU, clinicians commonly use therapeutic drugs that are mainly associated with regulating immune disorders (Guo et al, 2020;Zhang et al, 2021). Among them, the representative drugs in recent years have been glucocorticoids and thalidomide.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of RAU worldwide ranges from 5% to 66% (Bratel and Hakeberg, 2014), and it is approximately 20% in China (Xu et al, 2021). At present, to reduce the occurrence frequency of RAU, clinicians commonly use therapeutic drugs that are mainly associated with regulating immune disorders (Guo et al, 2020;Zhang et al, 2021). Among them, the representative drugs in recent years have been glucocorticoids and thalidomide.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant AN occurs in elderly patients with a rapidly, progressive velvety thickening of the flexural skin surfaces and oral mucosa unlike the younger, slowly occurring benign AN but patients as young as 30 years old with malignant AN has been reported. 8 Malignant AN has a well‐established association with internal malignancies, especially gastric adenocarcinoma, but an association with clear cell lung carcinoma, 9 bladder carcinoma, 10 pancreatic, ovary, esophageal, and renal cell carcinoma have also been reported. 11 The co‐existence of AN and BP had been rarely described.…”
Section: Discussionmentioning
confidence: 99%
“…2,18 An additional case of all 3 paraneoplastic conditions was reported in the setting of metastatic cervical cancer (HPV positive). 19 Per a recent case report and literature review, 20 there have only been 8 cases of acanthosis nigricans reported in bladder transitional cell carcinoma, [20][21][22][23][24][25][26][27] half of which have included oral malignant acanthosis nigricans. [20][21][22][23] Only one report of concurrent cutaneous and oral malignant acanthosis nigricans and triple palms in the setting of bladder cancer has been reported.…”
mentioning
confidence: 99%
“…19 Per a recent case report and literature review, 20 there have only been 8 cases of acanthosis nigricans reported in bladder transitional cell carcinoma, [20][21][22][23][24][25][26][27] half of which have included oral malignant acanthosis nigricans. [20][21][22][23] Only one report of concurrent cutaneous and oral malignant acanthosis nigricans and triple palms in the setting of bladder cancer has been reported. 20 Given the extensive conjunctival involvement and cutaneous papillomatosis in our patient, ours is a rarely reported case of concurrent malignant mucocutaneous acanthosis nigricans, tripe palms, and progressive papillomatosis in transitional cell bladder carcinoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation